Fine-scale staging of T-cell lineage commitment in adult mouse thymus - Yui, Mary A. (2010)
T cell development is marked by the loss of alternative lineage choices accompanying specification and commitment to the T cell lineage. Commitment occurs between the CD4 and CD8 double-negative (DN) 2 and DN3 stages in mouse early T cells. To determine the gene regulatory changes that accompany commitment, we sought to distinguish and characterize the earliest committed wild type DN adult thymocytes. A transitional cell population, defined by the first down-regulation of surface c-Kit expression, was found to have lost the ability to differentiate into dendritic cells (DC) and natural killer (NK) cells when cultured without Notch-Delta signals. In the presence of Notch signaling, this subset generates T lineage descendants in an ordered precursor-product relationship between DN2, with the highest levels of surface c-Kit, and c-Kit-low DN3 cells. These earliest committed cells show only a few differences in regulatory gene expression as compared to uncommitted DN2 cells. They have not yet established the full expression of Notch-related and T cell differentiation genes characteristic of DN3 cells before β-selection. Instead, the downregulation of select stem cell and non-T lineage genes appears to be key to the extinction of alternative lineage choices.